Analyzing Potato Market Participation, Market Surplus, and Market Outlet Choice on Small Farm Household Level in Lemo District, Southern Ethiopia - Chaimiso Demisse; Mesfin Melese; Mebratu Alemu; Afework Berhanu; Tamrat Sinore (Advances in Agriculture)
This study was aimed to analyze potato market participation, market surplus, and market outlet choice in Lemo District of southern Ethiopia. To achieve the objective, primary and secondary data sources were employed and 202 potato producers were selected following simple random sampling techniques. The collected data were analyzed by using Heckman second-stage and multivariate probit models to identify factors that determine potato market participation decision and potato farmer market outlet choice, respectively. The Heckman’s first-stage (probit) result indicates that education level, sex, membership in the cooperative, distance to the nearest market, remittent from family members, own transportation facilities, seed types, frequency of extension contact, lagged market price, and amount of credit that farm household used for potato production significantly (P<) determined producers’ participation in potato market. Heckman second-stage (OLS) result showed that education level, cooperative membership, family size, total cropland size, oxen owned, types of seed, and lagged market price were significantly (P<) determined potato marketed surplus. Multivariate probit results showed the probability to choose wholesalers (P<), retailers (P<), collectors (P<), and consumers (P<) market outlets who were significantly affected by age, educational levels, sex, farm experiences, distance to near market, family size, remittance, land size, product supplied to the market, own transport facility, and extension service. Therefore, we recommend that the government and concerned stakeholders should focus on promoting improved potato seed, encouraging education, promoting farmers’ cooperatives, empowering females, strengthening rural-urban infrastructure, and protecting informal labor trading.